A single day of excessive dietary fat intake reduces whole-body insulin sensitivity: the metabolic consequence of binge eating - Parry, S; Woods, R; Hodson, L; Hulston, C (MDPI, 2017)
Consuming excessive amounts of energy as dietary fat for several days or weeks can impair glycemic control and reduce insulin sensitivity in healthy adults. However, individuals who demonstrate binge eating behavior overconsume for much shorter periods of time; the metabolic consequences of such behavior remain unknown. The aim of this study was to determine the effect of a single day of high-fat overfeeding on whole-body insulin sensitivity. Fifteen young, healthy adults underwent an oral glucose tolerance test before and after consuming a high-fat (68% of total energy), high-energy (78% greater than daily requirements) diet for one day. Fasting and postprandial plasma concentrations of glucose, insulin, non-esterified fatty acids, and triglyceride were measured and the Matsuda insulin sensitivity index was calculated. One day of high-fat overfeeding increased postprandial glucose area under the curve (AUC) by 17.1% (p < 0.0001) and insulin AUC by 16.4% (p = 0.007). Whole-body insulin sensitivity decreased by 28% (p = 0.001). In conclusion, a single day of high-fat, overfeeding impaired whole-body insulin sensitivity in young, healthy adults. This highlights the rapidity with which excessive consumption of calories through high-fat food can impair glucose metabolism, and suggests that acute binge eating may have immediate metabolic health consequences for the individual.